2012
DOI: 10.1152/ajplung.00031.2011
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effect of protein kinase C on ENaC-mediated lung liquid regulation in the adult rat lung

Abstract: The aim of this work was to determine whether PKC activation is involved in the physiological regulation of LL volume in a whole lung preparation. Rat lungs were perfused with a modified Ringer solution, and the lumen was filled with the same solution without glucose. LL volume was measured during a control period and after modulating drugs were administered, and net LL transepithelial movement (Jv) was calculated. When the PKC activator PMA (10 Ϫ5 M) and the Ca 2ϩ ionophore ionomycin (10 Ϫ6 M) were instilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…For example, estrogen produced a 50% inhibition of 22 Na + uptake in pig kidney epithelial LLC-PK1 cells after PMA (PKC activator) treatment [43]. In the alveoli, it has been shown that PKC is involved in ENaC-mediated lung liquid regulation [44]. However, to our knowledge, no report has shown that the PKCδ isoform could regulate fluid absorption through the bronchial epithelia.…”
Section: Discussionmentioning
confidence: 98%
“…For example, estrogen produced a 50% inhibition of 22 Na + uptake in pig kidney epithelial LLC-PK1 cells after PMA (PKC activator) treatment [43]. In the alveoli, it has been shown that PKC is involved in ENaC-mediated lung liquid regulation [44]. However, to our knowledge, no report has shown that the PKCδ isoform could regulate fluid absorption through the bronchial epithelia.…”
Section: Discussionmentioning
confidence: 98%
“…The in situ perfused rat preparation used in these experiments has been described previously (75,89). All animal experiments were approved by independent committees.…”
Section: Measurement Of In Situ Lung Liquid Clearance In Ratsmentioning
confidence: 99%
“…Se ha descrito que los canales de sodio son elementos fundamentales en la regulación del edema, y que una función correcta de los mismos podría resolver este evento de forma vectorial (102)(103)(104)(105)(106). Aparentemente, se requiere la subunidad de Na-K ATPasa para la polarización celular y formación de uniones intercelulares, esenciales en la estabilización de la barrera (107)(108)(109)(110).…”
Section: Canales De Sodiounclassified